Ultrasonographic and haematology findings as an indicator of uterine torsion prognosis in cattle - de Carvalho, Jaqueline Candido [UNESP]; Lainetti, Patrícia de Faria [UNESP]; Alonso, Juliana de Moura [UNESP]; Souza, Fabiana Ferreira [UNESP]; Ferreira, João Carlos Pinheiro [UNESP] (Wiley, 2022)
Uterine torsion is considered an obstetric emergency. In severe cases, it compromises the survival of both the fetus and the dam. The purpose of the current report is to describe uterine torsion in an 8-year-old full-term pregnant Nelore cow, at 275 days of gestation, presenting physiological and behavioural changes for 12 hours. Physical examination revealed tachycardia, tachypnoea and mucoid vaginal discharge. On rectal examination, absent signs of fetal viability, increased ultrasonographic appearance of the uterine wall, separation of its layers and hyperechogenic placentomes showing rough borders were observed. Blood sample evaluation revealed biochemical changes. The postmortem examination confirmed severe uterine torsion with detachment of uterine wall layers and severe subendometrial haemorrhage. Haematology and biochemistry profiles and ultrasonographic findings were helpful in determining the severity of uterine damage. Ultrasound examination is a rapid, non-invasive and low-cost procedure that can be used to establish a prognosis while avoiding expensive and unsuccessful therapeutic approaches.
Keywords: diseases; farm animals; obstetrics